2021
DOI: 10.33448/rsd-v10i5.15014
|View full text |Cite
|
Sign up to set email alerts
|

Growth curves of different free-range chicken lineages by the Gompertz model

Abstract: The knowledge of the dynamics of animal growth over time can be done through non-linear equations. Thus, the objective was to describe and compare the growth of three free-range chicken lineages based on the Gompertz equation. 180 unsexed chickens assigned to three treatments (Pesadão Vermelho, Pescoço Pelado and Carijó Pesado lineages) in a randomized design with six replicates, with 10 birds per experimental unit. Broilers were weighed weekly (until 77 days of age), these data were used to estimate the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Based on Table 8 and Figure 6, the prediction of body weight of crossbred chicken from age 0-8 weeks was entirely accurate with a coefficient of determination of 0.9932 for crossbred resulting from crossing between Pelung rooster and Isa brown layer hens. The results of this study are not much different from previous studies in that the Gompertz function is very accurate in describing growth curves in various types of poultry (Michalczuk et al 2016;Eleroǧlu et al 2014;Masoudi & Azarfar 2017;N'dri et al 2018;Adenaike et al 2017;Urfa et al 2017;Anang et al 2017;Cyril et al 2021;Nguyen et al 2023;Brito et al 2021;Hagan et al 2022).…”
Section: The Effect Of Treatment On Body Weight Of Crossbred Chickenscontrasting
confidence: 64%
“…Based on Table 8 and Figure 6, the prediction of body weight of crossbred chicken from age 0-8 weeks was entirely accurate with a coefficient of determination of 0.9932 for crossbred resulting from crossing between Pelung rooster and Isa brown layer hens. The results of this study are not much different from previous studies in that the Gompertz function is very accurate in describing growth curves in various types of poultry (Michalczuk et al 2016;Eleroǧlu et al 2014;Masoudi & Azarfar 2017;N'dri et al 2018;Adenaike et al 2017;Urfa et al 2017;Anang et al 2017;Cyril et al 2021;Nguyen et al 2023;Brito et al 2021;Hagan et al 2022).…”
Section: The Effect Of Treatment On Body Weight Of Crossbred Chickenscontrasting
confidence: 64%
“…The production of broiler chickens in an alternative system is a strategy used by poultry farmers seeking to offer a product with characteristics different from those offered by the intensive poultry production system (TAVARES et al, 2015;BRITO et of 70 days for free-range chicken. According to the legislation, slow-growing birds of specific lines should be used for this purpose and should be slaughtered at 120 days at the oldest.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zuidhof et al [18] indicated that BW gain had increased by about 400% while the FCR has been reduced by 50% in the last 50 years, thus changing the growth dynamics of broilers. The constant genetic selection for the improvement of broilers' feed efficiency added up to the strategies employed in commercial operations to raise broilers has led many authors to compare the chickens' growth curves from genetically selected fast-growing [5,19] and native [20][21][22] broiler strains, in sexed and unsexed systems [4,23,24]. Nevertheless, reports about the growth of broiler chickens subjected to feeding control and raised under commercial tropical conditions are still scarce.…”
Section: Introductionmentioning
confidence: 99%